الحب بين التحليل النفسي والفلسفة: قراءة فلسفية معاصرة لتحليل لاكان البنيوي لمحاورة "المأدبة" - محرم، نشوى صلاح الدين محمد (جامعة القاهرة - فرع الخرطوم - كلية الآداب, 2022)
قمنا في هذا البحث بإظهار العلاقة بين الفلسفة والتحليل النفسي من خلال تصور جاك لاكان لمفهوم الحب بوصفه تحويلا من خلال قراءته التحليلية والبنيوية لمحاورة أفلاطون "المأدبة". وقد قام لاكان بالكشف عن بنية علاقة الحب كما ظهرت في المحاورة، ووصل من خلال ذلك إلى تطوير تصوره عن الحب بوصفه تحويلا وتطبيق هذا التصور في مجال التحليل النفسي. كما قدمنا رؤية تحليلية نقدية لتصورات لاكان عن الحب في محاورة "المأدبة"، وربطه بين المحلل النفسي وسقراط. وقد قمنا بذلك من خلال تقسيم البحث إلى مقدمة وأربع عناصر وخاتمة قدمنا فيها: أولا تمهيدا يتضمن توضيحا للمصطلحات الأساسية في نظريته عن التحليل النفسي وربطها بتصوراته المختلفة عن الحب. ثانيا تحليل لاكان البنيوي للخطابات المختلفة في المحاورة ثالثا نظرية لاكان عن الحب بوصفه تحويلا كما استمدها من تحليلاته للمحاورة. رابعا تطبيق هذا التصور عن الحب على جلسات التحليل النفسي وإبراز محوريته في العلاج وإبراز التوازي الذي يقيمه بين سقراط وبين المحلل النفسي. وقد تضمنت الخاتمة تأسيسا لمشروعية قراءة لاكان الجديدة عن الحب عند أفلاطون، وتوضيح للتشابهات والاختلافات بين تصور أفلاطون وتصور لاكان عن الحب كتحويل. In this research, we show the relationship between philosophy and psychoanalysis through Jacques Lacan's conception of love as “transference” through his analytical and structural reading of Plato's dialogue "The Symposium". Lacan revealed the structure of the love relationship as it appeared in the dialogue, and through this he developed his conception of love as transference and applied this conception in the field of psychoanalysis. We also presented a critical analytical view of Lacan's perceptions about love in the symposium, and the connection that he revieled between the psychoanalyst and Socrates. We did this by dividing the research into an introduction, four elements and a conclusion in which we presented: First, a prelude that includes illustrations of the basic terms in his theory of psychoanalysis and linking them to his different perceptions of love. Secondly, Lacan's structural analysis of the various discourses in the dialogue. Third, Lacan's theory of love as transference, as he derived it from his analyzes of the dialogue. Fourth, applying this conception of love to psychoanalytic sessions, highlighting its centrality in treatment, and highlighting the parallels that he establishes between Socrates and the psychoanalyst. The conclusion included a foundation for the legitimacy of Lacan's new reading of Plato's love, and an explanation of the similarities and differences between Plato's conception and Lacan's conception of love as transference.
Keywords: الفلسفة المعاصرة -- التحليل النفسي -- المشاعر الإنسانية -- لاكان، جاك، ت. 1981 م